UST-TSILMA FEMALE HEADDRESS: DESCRIPTION AND USE (MID-19TH TO EARLY 21ST CENTURY) - T. I. Dronova; Т. И. Дронова (Archaeology, Ethnology & Anthropology of Eurasia, 2017)
The study describes the headdresses worn by girls and women in a group of Russian Old Believers known as Bespopovtsy (Pomortsy, Priestless Brethren), who had moved from northwestern Russia to the Lower Pechora in the late 1700s, and currently live in the Ust-Tsilemsky District of the Komi Republic. Some headdresses were collected during my field studies in 2010–2014 in Ust-Tsilma villages; others, by A.V. Zhuravsky in the early 1900s (those are owned by Peter the Great Museum of Anthropology and Ethnography (Kunstkamera), St. Petersburg). A detailed description and analysis of headdresses and scarves are provided, as well as the ways they were worn and fastened, and their vernacular names. On the basis of this analysis, ethno-cultural ties of Russian Old Believers with Russian and non-Russian groups professing official Orthodoxy are examined. The functions of the headgear, related beliefs, and everyday and ritual use are discussed. The article is supplemented by stories told by informants about their clothing, and illustrated with originals photographs. В статье рассматриваются девичьи и женские головные уборы русских староверов-беспоповцев (поморцев), переселившихся на Нижнюю Печору в конце XVIII в. из северо-западных областей России и в настоящее время проживающих в Усть-Цилемском р-не Республики Коми. Основу работы составили полевые материалы, собранные автором в 2010–2014 гг. в усть-цилемских селах и деревнях, а также головные уборы из коллекции А.В. Журавского, сформированной в начале XX в., которая хранится в Музее антропологии и этнографии им. Петра Великого (Кунсткамера). В работе подробно описываются и анализируются женские головные уборы, в т.ч. платки, способы их ношения и крепления, приводятся локальные названия. Усть-цилемский кокошник существенно отличался от образцов, известных в других районах России, и при ношении всегда полностью закрывался платком, тогда как в других местностях это был самостоятельный убор, без дополнений в виде платка. Печорский повойник – свадебный головной убор невест. На ...